2018
DOI: 10.1080/20477724.2018.1427308
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping comparison ofMycobacterium lepraeisolates by VNTR analysis from nasal samples in a Brazilian endemic region

Abstract: This study analyzed the genetic diversity by MIRU-VNTR of Mycobacterium leprae isolates from nasal cavities and related to epidemiological and clinical data. The sample consisted of 48 newly diagnosed leprosy cases that tested positive for M. leprae PCR in nasal secretion (NS) attending to the National Reference Center of Dermatology Dona Libania (CDERM), Fortaleza, Brazil. Total DNA was extracted from NS of each patient and used for amplification of four M. leprae VNTR loci. Four clusters of M. leprae isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(47 reference statements)
0
7
1
Order By: Relevance
“…However, the importance of genotyping NS as well as skin biopsies or SSS to better understand transmission has been previously discussed (69), as the nasal respiratory route remains one of the most plausible modes of infection (12,13). In a recent study, skin biopsies and NS of patients were compared by VNTR typing and the authors found that out of 38 patients, differences between SSS and NS in seven loci were observed in 33 patients (70). Although the M. leprae genomes from SSS and NS analysed in our study were almost identical, we observed that genomes obtained from NS harboured more mutations, especially in previously reported (29) hypermutated genes.…”
Section: Discussioncontrasting
confidence: 46%
“…However, the importance of genotyping NS as well as skin biopsies or SSS to better understand transmission has been previously discussed (69), as the nasal respiratory route remains one of the most plausible modes of infection (12,13). In a recent study, skin biopsies and NS of patients were compared by VNTR typing and the authors found that out of 38 patients, differences between SSS and NS in seven loci were observed in 33 patients (70). Although the M. leprae genomes from SSS and NS analysed in our study were almost identical, we observed that genomes obtained from NS harboured more mutations, especially in previously reported (29) hypermutated genes.…”
Section: Discussioncontrasting
confidence: 46%
“…Among 38 patients, MLVA patterns were also available from nasal swabs, with the exclusion of alleles 6–3 and 18–8, not performed in this sample type and as described recently, difference in copy number of the alleles with highest DI was observed in the M . leprae genotypes when comparing both samples in a considerable number of patients [ 43 ]. Upon inclusion of the genotypes of M .…”
Section: Resultsmentioning
confidence: 99%
“…leprae genotypes present in skin biopsy and nasal secretion is described and discussed in detail elsewhere [ 43 ]. While all isolates presently presented four copies of (GGT)5, one nasal swab sample presented six copies of this allele [ 43 ] and although other alleles than that of four copies are described with very low frequency in Brazil [ 16 ], they are more frequent in countries like Thailand [ 27 ] and the Philippines [ 25 ]. Contrary to the single allele with two copies of 23–3 described by Lima et al [ 43 ], in 8% of our patients, a single copy of this marker was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations